(untitled) (Informatica, 2024)
The quality of invention and entrepreneurship of university students is an important factor in building an innovative society in China. In order to improve the quality of innovation and entrepreneurship of college students, a model of college students’ innovation and entrepreneurship quality based on artificial intelligence technology is constructed. The historical information data and real-time data streams of university students’ invention and entrepreneurship quality are collected from data sources such as management departments and service and collaborative organizations. Data processing methods pre-process the collected data and then fuse it with the collected data by association rule feature extraction methods. After the fusion, the components of the entrepreneurial quality model of college students are determined, 25 quality indicators are selected from five dimensions of innovation consciousness, entrepreneurship, emotional management, professional knowledge and practical ability to build a model of college students’ innovation and entrepreneurship quality, and Markov chain and fuzzy algorithm are used to assess college students’ invention and entrepreneurship quality. The results show that the model has an accuracy rate of more than 94% for feature extraction of association rules and a good clustering effect of indicators, which is able to enhance the invention and entrepreneurship quality of university students greatly and has a wide promotion value.